2015
DOI: 10.1007/s40415-015-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and ecological characteristics of potentially toxic invasive cyanobacterium Sphaerospermopsis aphanizomenoides (Forti) Zapomelová, Jezberová, Hrouzek, Hisem, Reháková & Komárková (Nostocales, Cyanobacteria) in Serbia

Abstract: This study investigates the morphology and occurrence of the potentially toxic invasive cyanobacterium recently detected in Serbia, Sphaerospermopsis aphanizomenoides (Forti) (Zapomelová et al. 2010), in correlation with several environmental parameters. The presence of this species was recorded during warm months in three of four studied sites in the Ponjavica River. It was found in a community with invasive Cylindrospermopsis raciborskii (Woloszynska) (Seenayya and Subba Raju 1972) and Raphidiopsis mediterra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…So far, the most northern reports of a mass development of C. raciborskii have come from Lake Balaton (46–47°N) in Hungary (Padisák & Reynolds ) and Alte Donau (48°N) in Vienna, Austria (Donabaum et al ). The abundance of S. aphanizomenoides is usually low in temperate water bodies, although it has recently been reported as a subdominant from a river in Serbia (44°N; Jovanović et al ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the most northern reports of a mass development of C. raciborskii have come from Lake Balaton (46–47°N) in Hungary (Padisák & Reynolds ) and Alte Donau (48°N) in Vienna, Austria (Donabaum et al ). The abundance of S. aphanizomenoides is usually low in temperate water bodies, although it has recently been reported as a subdominant from a river in Serbia (44°N; Jovanović et al ).…”
Section: Introductionmentioning
confidence: 99%
“…What is evident at the beginning of the twenty-first century is an increase in the trophic status and a decrease in depth along with an increased amount of sludge. These conditions have led to more intense and long-lasting blooms of potentially toxic cyanobacteria during the summer, but with the retention of relatively high taxa richness, especially in green algae [61,62,[67][68][69][70].…”
Section: Microalgae In Vojvodinamentioning
confidence: 99%
“…Periodically, it was dominant in this ecosystem. Its detailed morphological and ecological properties were presented in Jovanović et al [70]. As previously mentioned, R. raciborskii was first recorded in the Slatina, but in the Ponjavica River its bloom was recorded for the first time in Serbia in 2008 [61,62].…”
Section: Microalgae In Vojvodinamentioning
confidence: 99%
“…Reháková & Komárková was for the first time reported from lakes in Turkey and later considered as a bloom forming species in tropical and subtropical regions (de Figueiredo et al 2010;Cirés & Ballot 2016). Recent studies revealed its expansion toward temperate zone where it is commonly reported (Kaštovský et al 2010;Zapom elová et al 2012;Jovanovi c et al 2016;Budzy nska et al 2019).…”
Section: Introductionmentioning
confidence: 99%